Conditional Analysis for Mixed Covariates, with Application to Feed Intake of Lactating Sows - S. Y. Park; C. Li; S. M. Mendoza Benavides; E. van Heugten; A. M. Staicu (Journal of Probability and Statistics)
We propose a novel modeling framework to study the effect of covariates of various types on the conditional distribution of the response. The methodology accommodates flexible model structure, allows for joint estimation of the quantiles at all levels, and provides a computationally efficient estimation algorithm. Extensive numerical investigation confirms good performance of the proposed method. The methodology is motivated by and applied to a lactating sow study, where the primary interest is to understand how the dynamic change of minute-by-minute temperature in the farrowing rooms within a day (functional covariate) is associated with low quantiles of feed intake of lactating sows, while accounting for other sow-specific information (vector covariate).